Enhanced oral bioavailability of valsartan in rats using a supersaturable self-microemulsifying drug delivery system with P-glycoprotein inhibitors. (7th February 2020) - Goo, Yoon Tae; Song, Seh Hyon; Yeom, Dong Woo; Chae, Bo Ram; Yoon, Ho Yub; Kim, Chang Hyun; Park, Sun Young; Kang, Tae Hoon; Lee, Sangkil; Choi, Young Wook
Abstract: Valsartan (VST) is a poorly water-soluble drug and a P-glycoprotein (P-gp) substrate. To enhance the dissolution and oral absorption of VST, a novel supersaturable self-microemulsifying drug delivery system (Su-SMEDDS) was formulated. Based on the previously reported Su-SMEDDS composed of Capmul ® MCM (oil), Tween ® 20 (T20; surfactant), Transcutol ® P (cosurfactant), and Poloxamer 407 (supersaturating agent), P-gp inhibitory surfactants including Tween ® 80 (T80) and Cremophor ® EL (CR) were newly introduced to replace T20. All Su-SMEDDS formulations had a droplet size of <200 nm and showed rapid (>90% within 5 min) and pH-independent dissolution characteristics. The effective permeability coefficient (Peff ) in rat jejunum was obtained using an in situ single-pass intestinal perfusion study: Peff values of Su-SMEDDS-T20, Su-SMEDDS-T80, and Su-SMEDDS-CR were 2.3, 4.1, and 3.4 times greater, respectively, than that of the VST solution. After oral administration of various formulations to rats (equivalent dose of VST 10 mg/kg), plasma drug levels were measured by liquid chromatography-tandem mass spectrometry. The relative bioavailabilities of Su-SMEDDS-T20, Su-SMEDDS-T80, and Su-SMEDDS-CR were 262%, 470%, and 458%, respectively, compared with the VST suspension. Thus, we propose that the Su-SMEDDS-T80 formulation is a good candidate for improving the oral absorption of poorly water-soluble and P-gp substrate drugs such as VST. Graphical Abstract: